FINANCIAL AUDIT AND RECOVERY OF CLIENTS’ SMES FROM THE BANCO DE CREDITO - Cipriano Urtecho, Karhy (2015)
The thesis entitled “Financial Audit and its Impact on Credit Recovery of SME Clients from the Banco de Credito - Lambayeque Region” managed to verify the way that financial audit helps determine the presence of SME defaulting debtors from the Banco de Credi-to- Lambayeque Region, where the scientific research method was used. The thesis in the theoretical con-ceptual part, was developed by gathering information from different specialists, their contributions helped to consolidate the development of the variables: Finan-cial Audit and Credit Recovery of SMB customers- supported in its different indicators- and clarifying the contribution of the audit with a systematic and disciplined approach. The Fieldwork part used the survey technique- with the questionnaire instrument- that consisted on 20 questions, it allowed taking data from the selected sample; likewise the contrasting of hypothesis was carried out to arrive at conclusions and recommendations. Finally, the contribution of the research is to demonstrate how the Banco de Credito must use financial audit to control the placement of capital in small and medium enterprises.